Surface relief gratings inscription in linear and crosslinked azo modified epoxy‐isocyanate polymers - Sáiz, Luciana M; Ainchil, Paula; Zucchi, Ileana A; Oyanguren, Patricia A; Galante, María J (Journal of polymer science. Part B, Polymer physics, 2015)
This work analyses the SRG forming ability of a linear and a crosslinked polymer, both based on the same azo chromophore (Disperse Red 19, DR19) and diisocyanate (4,4'‐metilen‐bis(cyclohexyl isocyanate), DI) with similar glass transition temperature values. The effect of the experimental and geometrical parameters (such as beams polarization direction and interference pattern spacing) on the surface modulation process was examined as well. The absence of photodegradation or bleaching was corroborated by comparing Raman spectra inside and outside the SRG zone. Being a very important subject matter, the influence of crosslinking on the inscription rates and thermal stability of SRGs was investigated. Crosslinked films with an interesting modulation and good grating stability, even at high temperatures (160 °C), were obtained. Gratings shape was retained, and significant diffraction was still observed even well above the Tgof the bulk sample. © 2015 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys. 2015, 53, 587–594